The Relationship between Farmer’s Characteristics and Institutions on the Sustainability of Pasundan Cattle Business in Purwakarta Regency (Case in the Tegal Saluyu Group 1 and 2 of Tegalsari Village, Tegalwaru District, Purwakarta Regency) - HASANAH, KINSA RAEHAN; Sulaeman, Mumun Munandar; Wiyatna, Muhamad Fatah (Fakultas Peternakan, Universitas Padjadjaran, 2024)
The research entitled